The Influence of the Quality of Financial Accounting Learning and Academic Achievement on the Financial Self-Efficacy of University Accounting Students Muhammadiyah Makassar - Hajrah, Hajrah; Nerinza, Nerinza; Asrini, Asrini; Khairiyah, Nurul Mifta; Muchran, Muchriana (Jurnal Penelitian IPTEKS, 2024)
This research aims to determine: (1) the influence of the quality of financial accounting learning on financial self-efficacy, (2) the influence of academic achievement on financial self-efficacy. The population in this study was 226 accounting students from the class of 2020, the research sample was 69 students with sample determination using the Slovin formula. The method used is multiple linear regression analysis with the help of SPSS Version 26. Based on the research results, it shows that the Quality of Financial Accounting Learning has no partial effect on Financial Self Efficacy. Meanwhile, Academic Achievement partially influences Financial Self Efficacy.